Addressing the global snakebite crisis with geo-spatial analyses – Recent advances and future direction. (September 2021) - Pintor, Anna F.V.; Ray, Nicolas; Longbottom, Joshua; Bravo-Vega, Carlos A.; Yousefi, Masoud; Murray, Kris A.; Ediriweera, Dileepa S.; Diggle, Peter J.
Abstract: Venomous snakebite is a neglected tropical disease that annually leads to hundreds of thousands of deaths or long-term physical and mental ailments across the developing world. Insufficient data on spatial variation in snakebite risk, incidence, human vulnerability, and accessibility of medical treatment contribute substantially to ineffective on-ground management. There is an urgent need to collect data, fill knowledge gaps and address on-ground management problems. The use of novel, and transdisciplinary approaches that take advantage of recent advances in spatio-temporal models, 'big data', high performance computing, and fine-scale spatial information can add value to snakebite management by strategically improving our understanding and mitigation capacity of snakebite. We review the background and recent advances on the topic of snakebite related geospatial analyses and suggest avenues for priority research that will have practical on-ground applications for snakebite management and mitigation. These include streamlined, targeted data collection on snake distributions, snakebites, envenomings, venom composition, health infrastructure, and antivenom accessibility along with fine-scale models of spatio-temporal variation in snakebite risk and incidence, intraspecific venom variation, and environmental change modifying human exposure. These measures could improve and 'future-proof' antivenom production methods, antivenom distribution and stockpiling systems, and human-wildlife conflict management practices, while simultaneously feeding into research on venom evolution, snake taxonomy, ecology, biogeography, and conservation. Highlights: Many knowledge gaps remain on snake distributions and spatial snakebite variation. Targeted data collection and high resolution spatial models are needed. Maps of snake distributions, bite incidence, and vulnerable populations are needed. Area-specific antivenom delivery requires studies on spatial venom variation. Human welfare and snake conservation require spatial management of conflict.